The social function in the brazilian experience and its impact on the re-signification of contratual freedom in the 30 years of the 88 Constitution - Andrade, Gustavo Henrique Baptista (2018)
With central theme on the functionalization of institutes of private law, the present paper deals more specifically on the social function, constitutional principle linked to the right of property and consequently to the contract, instrument of the circulation of goods. Follwing a strong historical and spacial contingency, the social function enters in the Brazilian legal order through the Constitutions of the twentieth century. The principle of the social function of the contract inscribed in the 2002 Civil Code (article 421), prescribes commitments for the community, not only imposing limits, but sometimes restricting the possibility of contracting, which is corroborated by the paragraph in the article 2.035 of the same Code. The functional perspective allows a re-signification of the traditional categories of private law following the constitutional axiological table, constructing adequate answers to the most varied concrete cases.